2013
DOI: 10.2135/cropsci2012.10.0593
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation and Genotype × Environment Interactions for Seed Phytosterols in Sunflower

Abstract: Phytosterols are important dietary components. This research was aimed at estimating genetic variation and genotype × environment interactions for phytosterol content and profile in sunflower (Helianthus annuus L.). Twenty‐two commercial hybrids were grown in six locations in southern Spain. The effect of genotypes was significant for phytosterol content and concentration of most phytosterols. Genotype × location interaction was significant for the concentration of campesterol, stigmasterol, Δ7‐stigmastenol, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…a). Similar association was reported by Velasco et al (), who suggested that germplasm with low seed yield or low oil content might be associated with higher oil phytosterol content, while evaluated 22 hybrids in six locations in southern Spain. Environmental conditions for high yield and oil also produce a high phytosterol content per grain.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…a). Similar association was reported by Velasco et al (), who suggested that germplasm with low seed yield or low oil content might be associated with higher oil phytosterol content, while evaluated 22 hybrids in six locations in southern Spain. Environmental conditions for high yield and oil also produce a high phytosterol content per grain.…”
Section: Resultssupporting
confidence: 86%
“…Nolasco et al () observed variations in these compounds between 3513 and 4936 mg kg −1 oil in hybrids from different environments. In the same species, Velasco et al () reported a variation from 2954 to 3810 mg kg −1 kernel in 22 commercial hybrids grown in six environments. Roche et al (2010) found differences of up to 1180 mg of phytosterols (kg seed) −1 due to changes in sowing date in sunflower.…”
Section: Introductionmentioning
confidence: 96%
“…However, oil phytosterol content does not provide useful genetic information, as the trait depends upon the phytosterol content in the seeds, the oil content in the seeds, and the efficiency of the oil extraction method. For this reason, methods for the analysis of phytosterols in seeds have been developed and used for germplasm evaluation and genetic analyses [9,[15][16][17]. This is the approach that we have also used for studying variability in Jatropha germplasm.…”
Section: Resultsmentioning
confidence: 99%
“…Broad sense heritability was estimated in 0.72 by Merah, et al (2012) and 0.85 by Velasco, et al (2013). Amongst the main factors influencing seed phytosterol content, Roche, et al (2006;2010b) found that higher temperatures enhanced phytosterol accumulation, whereas water stress has been also found to favour phytosterol accumulation in sunflower seeds (Roche, et al, 2006).…”
Section: Variability For Seed Phytosterol Content In Sunflower Germplasmmentioning
confidence: 97%
“…Merah, et al (2012) reported a variation from 1523 to 2490 mg kg −1 seed (whole achene) in a population of recombinant inbred lines. Other studies based on the analysis of seed kernels have reported ranges of variation from 1426 to 4710 mg kg −1 kernel in 87 sunflower inbred lines (Fernández-Cuesta, et al, 2012a), from 2,179 to 3555 mg kg −1 kernel in 12 confectionery landraces (Fernández-Cuesta, et al, 2012b), from 2954 to 3810 mg kg −1 kernel in 22 commercial hybrids (Velasco, et al, 2013), from 1319 to 5119 mg kg −1 kernel in 985 accessions of a world collection , and from 1344.0 to 2942.5 mg kg −1 kernel in a collection of 137 Spanish landraces of confectionery sunflower .…”
Section: Variability For Seed Phytosterol Content In Sunflower Germplasmmentioning
confidence: 98%